Innovating Sustainably: The Role of Generative Design in Sustainable Technology Development - Indrajitsinh J. Jadeja; Nirav P. Maniar; Bhumika S. Zalavadia (International Journal of Machine Systems and Manufacturing Technology, 2025)
As industries strive for sustainability, generative design has emerged as a transformative approach in engineering, offering solutions that minimize environmental impact while optimizing product performance. Based on established features, including material, size, weight, and performance standards, generative design generates an immense amount of design options using machine learning and artificial intelligent algorithms. Unlike traditional design, which relies on human intuition, generative design automates the exploration of solutions, ensuring material efficiency, energy optimization, and emission reductions. This paper highlights the key role of generative design in sustainable technology development, illustrating its impact across various sectors, including architecture, automotive, aerospace, and consumer products. In these industries, generative design facilitates lighter, more energy-efficient products, reduces waste, and promotes a circular economy by creating products that are easier to recycle or repair. The design process involves defining sustainability goals, inputting parameters, simulating designs, and refining the most optimal solutions, ensuring that products meet both functional and environmental criteria. However, challenges such as high computational demands and the need for accurate data remain. Despite these hurdles, generative design represents a significant step toward achieving sustainable technological innovation. By optimizing design processes for material and energy efficiency, it aligns with the principles of a circular economy, paving the way for a future where industries can significantly reduce their ecological footprints. Embracing generative design fosters a culture of responsible innovation. Through automated, performance-driven variations, generative design has the potential to completely transform product creation. This article examines the role of generative design in environmentally conscious development. It also looks at the main advantages, including reducing carbon emissions, conserving resources, and integrating the circular economy, as well as the implementation difficulties, such adoption hurdles and computation complexity. In the end, generative design is a potent instrument for promoting sustainability and ushering in a new era of technology innovations that are clever, effective, and conscious of the environment.
Keywords: Energy optimization; circular economy; generative design; material efficiency; sustainable technology